Sargassum aquifolium Extract Prevents Elevated Cholesterol Levels and Blood Vessel Thickening in Rats Fed an Atherogenic Diet - Muhamad Firdaus; Rahmi Nurdiani; Aulia Savira; Firyal Hanifah (The Journal of Pure and Applied Chemistry Research, 2023)
Hypercholesterolemia is a health disorder in which cholesterol in the blood increases beyond normal limits. This disorder chronically can cause atherosclerosis. Sargassum aquifolium contains bioactive that can prevent an increase in blood cholesterol levels. This study aimed to prevent the increasing cholesterol levels and changes in the blood vessel profile of rats fed an atherogenic diet by S. aquifolium extract. S. aquifolium was obtained from Ekas Bay. Rattus norvegicus 2-3 months ages used in this study. Normal rats were fed an atherogenic diet for four months to produce an animal hypercholesterolemia model. The phytochemical profile was screened based on the Harborne method. Identity of bioactive determined by HPLC-HRMS. The parameters observed were cholesterol levels and blood vessel profiles. The juice of S. aquifolium contained steroids, saponins and tannins and their bioactive showed anticholesterolemic. Rats given an atherogenic diet had increased cholesterol levels. Administration S. aquifolium juice twice a day can reduce cholesterol levels and prevent the thickening of the aorta and arteries. In conclusion, S. aquifolium juice contains bioactive compounds and administration of S. aquifolium juice twice a day prevents an increase in cholesterol and damage to the aortic and arterial profiles.